Chronique de l’UNESCO (Fiep Bulletin - online, 2015)
The reason for an international recommendation on the situation of the teaching personnel, by rené Maheu. The Director General of UNESCO, while presiding over the Opening Session of the inter-Governmental Conference on the situation of the teaching personnel, held at the seat of that Organization in Paris, From 25th September to 5th October 1966, delivered there a remarkable speech.